The designation of SiP prototype verification platform based on FPGA - Yang Chuwei; Zhang Meijuan; Hou Qingqing (Dianzi Jishu Yingyong, 2022)
With the growing demand of embedded system miniaturization and the performance of analog-to-digital/digital-to-analog converter(ADC/DAC), it is a big problem how to improve the reliability of ADC/DAC signal transmission, increase the function configurability and signal processing reconfigurability on the premise of reducing system volume and power consumption. Thus, this paper designs a system in package(SiP) prototype verification platform based on FPGA, used to verify the feasibility and reliability of this SiP architecture.